Creation of an interspecific hybrid of Capsicum annuum L. and C. frutescens L. using biotechnological approaches - E. A. Dzhos; D. V. Shumilina; O. N. Pyshnaya; M. I. Mamedov; A. A. Baikov; A. A. Matyukina (Овощи России, 2021)
Relevance. Pepper is a common crop both for fresh consumption and for the preparation of spices. Recently, along with the increasing popularity of C. annuum L. pepper, there is increasing interest in other species of this genus, which have a number of breeding and important properties. The most important method of enriching the gene pool of cultivated plants is distant hybridization, through which valuable traits are transferred from wild species to cultivated ones. The development of a new variety is a lengthy process, stretching over several years. In this regard, breeders have faced the challenge of obtaining pure lines to create a pepper hybrid with desired properties by applying modern biotechnological methods that will accelerate this process. One of them is the method of microspore culture, which allows mass production of haploid plants, reducing the time for creating constant parental lines.Material and methods. The aim of the work was to create an interspecific hybrid of hot pepper (C. annuum L. x C. frutescens L.) with high ornamental properties, a complex of economically valuable traits, with good taste qualities. The research was carried out in the film greenhouse of FSBSI FSVC in the Moscow region. The research material was a variety population of hot pepper Capsicum frutescens Cz-544-14, used as a paternal line, which was heterogeneous, and a pure line of C. annuum L. (Pb-551) created by classical breeding.Results. The pepper hybrid F1 Christmas bouquet was created as a result of hybridization of species parental forms obtained by different methods (biotechnological and classical). To accelerate the production of an aligned paternal form of C. frutescens L., the technology of doubled haploids through microspore culture was used. As a result, doubled haploid plants meeting the planned model (compact low habit, purple fruit colouring in technical ripeness and red in biological ripeness) were obtained. The resulting hybrid combined all the necessary economic features: high ornamentality, compactness, bouquet arrangement of fruits, high taste and aroma. Thus, the use of remote interspecific hybridization in the breeding process in combination with biotechnological approaches can accelerate the production of new forms of hot peppers that meet the demands of the market.